Simulation of Diffusion Mechanism and Heterogeneous Dynamics in Network-forming Liquid - Ha, Nguyen Thi Thanh; Dung, Nguyen Anh; Bau, Nguyen Quang; Hung, Pham Khac (VNU Journal of Science: Mathematics - Physics; Vol 32 No 4, 2016)
Abtract : We have studied the diffusion mechanism in network-forming liquids via molecular dynamics simulation. Two models of silica liquid at temperatures of 2600 and 3500 K have been constructed. The motion of atoms is analyzed through reactions SiO x ®SiO x ±1 , OSi y ®OSi y ±1 and coordination cells. It was shown that the reactions happen not randomly in the space, but they occur more frequently with some coordination cells and bonds Si-O. This effect enhances upon lowering the temperature. The number of reactions happening in the coordination cells is strongly correlated with the mobility of CC atom. We found that there are large rigid clusters which compose of immobile atoms and exist for long time. Further, the dynamics heterogeneity (DH) is determined via sets of: (1) most mobile or immobile atoms; (2) atoms belonging to large rigid clusters. We show that the percolation rigid cluster responds to the dynamical slowing down present near glass-transition. Keywords: Simulation, silica, liquid, dynamic heterogeneity, rigid cluster.